Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Ika Permatasari; Dian Puspitasari (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2012)
AbstractThis research aims to analyze the affect between working capital management as measured by current ratio (CR), cash flow ratio (CFR), and debt to equity ratio (DER) to profitability as measured by value added (VA). The sample used was manufacturing company listed on Indonesia Stock Exchange period 2009-2011. The analysisis using logistic regression. The results show thatcurrent ratio had negativeeffect on the profitability and cash flow ratio had positiveeffect on the profitabilityratio. However, debt to equity ratio had no effect on profitability.